A new species Ctenophora wojtaliae sp. nov. from a highly alkaline Göydün Spring, Sivas in Republic of Türkiye contributes to the diversity of Ctenophora (Fragilariaceae: Bacillariophyta) - Solak, Cüneyt Nadir; Hamilton, Paul Brian; Mercan, Deniz; Arslan, Naime; Kusber, Wolf-Henning (Phytotaxa, 2026)
A new Ctenophora wojtaliae sp. nov. is described from a unique microenvironment in the highly alkaline (pH 9.4) Göydün spring in the Eastern Anatolia. Valves of C. wojtaliae are linear and slightly lanceolate, with broadly rounded apices. The new taxon is similar to Ctenophora pulchella (Kützing) D.M.Williams & Round, C. saxonica (Kützing) D.M.Williams & Van de Vijver, C. sinensis B.Liu & D.M.Williams and C. subula (Sande Lacoste & Suringar) D.M.Williams & Van de Vijver. Unlike the other taxa, C. wojtaliae has longer specimens and a thickened ridge at the central area form a rectangular not circular structure.